1883 Dakota Terr. Rev. Code 684 - (:unkn) unknown (My University, 1883)
Penal Code, § 457: Prohibited the concealed carry of any fire-arms or any sharp or dangerous weapon usually employed in attack or defense of the person. Violators guilty of a misdemeanor.
Keywords: CARRY - CONCEALED